Increasing Financial Inclusion in the General Business Environment - Rika Rahayu; Maratus Zahro; Budiyanto Budiyanto (Asian Journal of Management, Entrepreneurship and Social Science, 2023)
This study aims to analyze increasing financial inclusion in the general business environment. This research is a quantitative research with the hypothesis that there is an influence between financial literacy, financial technology, intensity of social media, gender, education, income, type of business, trust on financial inclusion and there is an influence between financial inclusion and income increase. The variables used in this study include endogenous variables, namely financial literacy, financial technology, intensity of social media, income, trust and financial inclusion. The exogenous variables are income variables. The results of this study are financial literacy has no effect on financial inclusion but has an effect on income, financial technology has no effect on financial inclusion but has an effect on income, trust has no effect on financial inclusion but has an effect on income, increased income has an effect on financial inclusion and has an effect on income. The intensity of social media has no effect on financial inclusion but has an effect on income. Financial inclusion has an effect on income.